Sistem Informasi Transparansi Dana Desa Kabupate Sumenep Berbasis Android - Arda Gusema Susilowati; Purnomo Hadi Susilo (Universitas Islam Lamongan, 2022)
From this modern and sophisticated era the village inspired writers do not have to make benner to publish it to the community, just open the internet and enter the data into the Android application Village Fund Transparency in Kab. Sumenep online and the general public can be accessed. This system is about the budget village funds in an online android application, for people who want budget funds in their villages including in other villages.The process of this system works, the village admin must first log in unless the village admin user name and password are created by superadmin. After that, the admin will manage the village fund budget data then the admin can input the village budget data into the application. Basically, the author issued this information system in addition to facilitate the process of inputting data on village budget funds, the author also wants to introduce the progress of the internet, one of which is based on Android. Need everyone, from any group can use the internet positively.